Evolution of Ecosystem Services in a Mediterranean Cultural Landscape: Doñana Case Study, Spain (1956-2006) - Gómez-Baggethun, Erik; Martín-López, Berta; Lomas, Pedro L.; Zorrilla, Pedro; Montes, Carlos (IntechOpen, 2011)
None